Update of the position paper on arterial hypertension and erectile dysfunction. Issue 7 (July 2020) - Viigimaa, Margus; Vlachopoulos, Charalambos; Doumas, Michael; Wolf, Jacek; Imprialos, Konstantinos; Terentes-Printzios, Dimitios; Ioakeimidis, Nikolaos; Kotsar, Andres; Kiitam, Urmo; Stavropoulos, Konstantinos; Narkiewicz, Krzysztof; Manolis, Athanasios; et al.
Abstract : N/A: Sexual health is an integral part of overall health, and an active and healthy sexual life is an essential aspect of a good life quality. Cardiovascular disease and sexual health share common risk factors (arterial hypertension, diabetes mellitus, dyslipidemia, obesity, and smoking) and common mediating mechanisms (endothelial dysfunction, subclinical inflammation, and atherosclerosis). This generated a shift of thinking about the pathophysiology and subsequently the management of sexual dysfunction. The introduction of phosphodiesterase type 5 inhibitors revolutionized the management of sexual dysfunction in men. This article will focus on erectile dysfunction and its association with arterial hypertension. This update of the position paper was created by the Working Group on Sexual Dysfunction and Arterial Hypertension of the European Society of Hypertension. This working group has been very active during the last years in promoting the familiarization of hypertension specialists and related physicians with erectile dysfunction, through numerous lectures in national and international meetings, a position paper, newsletters, guidelines, and a book specifically addressing erectile dysfunction in hypertensive patients. It was noted that erectile dysfunction precedes the development of coronary artery disease. The artery size hypothesis has been proposed as a potential explanation for this observation. This hypothesis seeks to explain the differing manifestation of the same vascular condition, based on the size of the vessels. Clinical presentations of the atherosclerotic and/or endothelium disease in the penile arteries might precede the corresponding manifestations from larger arteries. Treated hypertensive patients are more likely to have sexual dysfunction compared with untreated ones, suggesting a detrimental role of antihypertensive treatment on erectile function. The occurrence of erectile dysfunction seems to be related to undesirable effects of antihypertensive drugs on the penile tissue. Available information points toward divergent effects of antihypertensive drugs on erectile function, with diuretics and beta-blockers possessing the worst profile and angiotensin receptor blockers and nebivolol the best profile.